Understanding nighttime methane signals at the Amazon Tall Tower Observatory (ATTO) - S. Botía; C. Gerbig; J. Marshall; J. V. Lavric; D. Walter; D. Walter; C. Pöhlker; B. Holanda; G. Fisch; A. C. de Araújo; M. O. Sá; P. R. Teixeira; et al. (Atmospheric Chemistry and Physics, 2020)
Methane (CH4) atmospheric mixing ratio measurements are analyzed for the period between June 2013 and November 2018 at the Amazon Tall Tower Observatory (ATTO). We describe the seasonal and diurnal patterns of nighttime events in which CH4 mixing ratios at the uppermost (79 m a.g.l.) inlet are significantly higher than the lowermost inlet (4 m a.g.l.) by 8 ppb or more. These nighttime events were found to be associated with a wind direction originating from the southeast and wind speeds between 2 and 5 m s−1. We found that these events happen under specific nighttime atmospheric conditions when compared to other nights, exhibiting less variable sensible heat flux, low net radiation and a strong thermal stratification above the canopy. Our analysis indicates that even at wind speeds of 5.8 m s−1 the turbulence intensity, given by the standard deviation of the vertical velocity, is suppressed to values lower than 0.3 m s−1. Given these findings, we suggest that these nighttime CH4 enhancements are advected from their source location by horizontal nonturbulent motions. The most likely source location is the Uatumã River, possibly influenced by dead stands of flooded forest trees that may be enhancing CH4 emissions from those areas. Finally, biomass burning and the Amazon River were discarded as potential CH4 sources.